2021
DOI: 10.2196/26874
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy in Canada: Content Analysis of Tweets Using the Theoretical Domains Framework

Abstract: Background With the approval of two COVID-19 vaccines in Canada, many people feel a sense of relief, as hope is on the horizon. However, only about 75% of people in Canada plan to receive one of the vaccines. Objective The purpose of this study is to determine the reasons why people in Canada feel hesitant toward receiving a COVID-19 vaccine. Methods We screened 3915 tweets from public Twitter profiles in Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 26 publications
8
189
1
6
Order By: Relevance
“…The vaccine opposing content on Twitter was steadily increasing during the first half of 2020; thus, requiring thematic analysis of such content [66]. The discourse analysis of Griffith et al (2021) for COVID-19 VH tweets found that concerns over safety, mistrust of governments and drug manufacturers, and insufficient knowledge about vaccines were the critical drivers of VH [67].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine opposing content on Twitter was steadily increasing during the first half of 2020; thus, requiring thematic analysis of such content [66]. The discourse analysis of Griffith et al (2021) for COVID-19 VH tweets found that concerns over safety, mistrust of governments and drug manufacturers, and insufficient knowledge about vaccines were the critical drivers of VH [67].…”
Section: Discussionmentioning
confidence: 99%
“…Reliable and accurate information on social media is often mixed with inaccurate, conspiratorial, incomplete, or biased messages [22]. A recent study evaluating vaccine hesitancy through content analysis of tweets in Canada identified major themes including safety, suspicion of economic or political motivation, knowledge deficit, opinions of authority figures, and lack of liability from pharmaceutical companies [25]. This study demonstrates the significant utility of using Twitter to better understand vaccine hesitancy at a population level [25].…”
Section: Introductionmentioning
confidence: 85%
“…A recent study evaluating vaccine hesitancy through content analysis of tweets in Canada identified major themes including safety, suspicion of economic or political motivation, knowledge deficit, opinions of authority figures, and lack of liability from pharmaceutical companies [25]. This study demonstrates the significant utility of using Twitter to better understand vaccine hesitancy at a population level [25]. However, a broader reaching and deeper understanding of current patterns of communication that characterize the immunization debate on social media platforms is needed to inform public health interventions aimed toward influencing attitudes on immunization [15,17,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they noticed that rural individuals who did not have permitted residency (Hukou) in Shanghai showed more concerns about the side effects, safety, and effectiveness of vaccines compared to local residents of Shanghai. Janessa et al [36] sought to uncover the reasons for COVID-19 vaccine hesitancy in Canada. Using the Theoretical Domains Framework, they analyzed the contents of 3915 tweets based on knowledge, beliefs on consequences, environmental context and resources, social influence, and emotion.…”
Section: Covid-19 Vaccine Hesitancymentioning
confidence: 99%